Evaluation of different packages of health education intervention on the smoking behavior of some "smokers" in selected barangays in Pasay City - Imperio, Rhodie H. (1986)
This study evaluated the effects of 4 packages of Health Education Intervention (HEI) on smoking behavior of some smokers in selected barangays of Pasay City, Metro Manila, Philippines. The HEI consisted of 2 major approaches: (1) the Group Approach with films, slides, printed matter and lectures of a physician and a health educator; and (2) the Pamphlet Approach with printed matter only. Each approach was divided into 2 groups, 1 with biweekly follow-ups spread throughout the 3-month duration of the study and the other without follow-up, making 4 treatment groups. The treatment groups were as follows: (1) Group I - Group Approach with follow-up, (2) Group II - Group Approach without follow-up, (3) Group III - Pamphlet Approach with follow-up, and (4) Group IV - Pamphlet Approach without follow-up. A control group (Group V) was added for purposes of comparison. The study employed a pre-test and post-test quasi experimental design. Results showed that Group Approach with follow-up (Group I) proved to be the most effective approach in causing smoking behavior change both in terms of total quit rate and total mean percent reduction (30-100 reduction from baseline). The order of success in quit rates was as follows: Group I , 52.3 ; Group III, 20.9 ; Group II, 12.8 ; and Group IV, 6.3 . When the mean percent reduction was considered, Group I again achieved the highest reduction of 67.8 compared to Groups II, III and IV which had almost comparable reductions of 44.1, 44.6 and 47.2 , respectively. Surprisingly, the control group, in the absence of HEI, had a quit rate of 10 , but the total mean percent reduction was only 20.7. Thus, all 4 treatment groups still proved to be significantly better than the control group in achieving total change in behavior. Significant differences were observed in the patterns of change in smoking behavior between Group Approach and Pamphlet Approach with follow-ups. The light and moderate smokers in Group Approach had greater mean reductions than their counterparts in the Pamphlet Approach, but the heavy smokers in both groups had comparable mean reductions. The greatest total mean reduction was experienced by the heavy smokers in both groups, but the highest quit rate was among the light smokers.